Humanistic Digital Governance - Dennis J. Snower; Paul Twomey (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We identify an important feature of current digital governance systems: “third-party funded digital barter”: consumers of digital services get many digital services for free (or underpriced) and in return have personal information about themselves collected for free. In addition, the digital consumers receive advertising and other forms of influence from the third parties that fund the digital services. The interests of the third-party funders are not well-aligned with the interests of the digital consumers. This fundamental flaw of current digital governance systems is responsible for an array of serious problems, including inequities, inefficiencies, manipulation of digital consumers, as well as dangers to social cohesion and democracy. We present four policy guidelines that aim to correct this flaw by shifting control of personal data from the data aggregators and their third-party funders to the digital consumers. The proposals cover “official data” that require official authentication, “privy data” that is either generated by the data subjects about themselves or by a second parties, and “collective data.” The proposals put each of these data types under the individual or collective control of the data subjects. There are also proposals to mitigate asymmetries of information and market power.
Keywords: 330; digital governance; digital services; personal data; digital service providers; market power; advertising; preference manipulation